Kontribusi Mahasiswa KKN dalam Pengembangan Pendidikan Nonformal Berbasis Masjid - Aibdi Rahmat; Yusnelma Eka Afri; Slamet Ferdianto; Diva Fazkia; Siti Nurrosmah Abdini; Andini Dwi Sahara; Hana Kharmila; Firnanda Astuti; Najwa Rahmatunnisa; Muspani Muspani; Jundi Mega Bramasto; Ferdyansyah Ferdyansyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2026)
Mosque-based non-formal education through Taman Pendidikan Al-Qur’an (TPQ) and Remaja Islam Masjid (RISMA) plays a strategic role in shaping religious character, strengthening Islamic values, and encouraging youth participation in community-based religious activities. However, its implementation often faces several challenges, such as limited teaching staff, low consistency among youth members, and the need for more structured learning activities. This study aims to describe the contribution of KKN students in developing mosque-based non-formal education at Al-Muqorrabin Mosque, Bengkulu. The research used a descriptive qualitative approach through participatory observation, interviews, and documentation. The findings show that the presence of KKN students had a positive impact on the development of TPQ and RISMA activities. TPQ children became more active in learning to read the Qur’an, especially in improving pronunciation and understanding basic tajwid. The teaching and learning process also became more organized and interactive. In addition, RISMA activities became more consistent, with around 12–15 teenagers participating in weekly programs. The involvement of KKN students also increased the spirit of the congregation in enlivening mosque activities. This study concludes that KKN students function as transformative and sociocultural agents of change in strengthening mosque-based non-formal religious education.